POLITICAL AND LEGAL DEVELOPMENTS IN MINERAL AND COAL MINING LAWS: A CRITICAL REVIEW - Natsir, Muhammad; Ilahi, Andi Hidayat Anugrah; Adnas, Titien Pratiwi (Diponegoro Law Review, 2024)
The revision of Indonesia’s Mineral and Coal Mining Law (Law Number 3 of 2020) has generated significant debate and resistance, especially from 2019 through the initial phases of the COVID-19 pandemic in 2020. Significant concerns encompass heightened corruption risks, compromised environmental protections, dependence on foreign labor, reduced community rights in mining regions, and challenges to democratic and decentralized governance structures. This study rigorously analyses the legal and practical implications of the law, concentrating on its application within the nickel mining industry. This approach employs a juridical-normative framework, integrating literature reviews and observational methods to evaluate recent legal cases and the effects of policy changes. The findings indicate that although the law is designed to simplify licensing procedures and encourage investment, it also presents issues related to diminished regional autonomy, possible environmental harm, and social disparities. The highlighted issues reveal Indonesia’s dependence on extractive industries, which starkly contrasts the global movement towards sustainable practices. The research underscores the necessity for regulatory reforms that harmonize economic development with environmental sustainability and fair resource management, providing critical insights for policymakers, legal professionals, and industry participants.